Scientometric Portrait of Dr. S.V. Kamat: A Distinguished Defence and Material Scientist - Sarode, Anand R; Khaparde, Vaishali S (Journal of Data Science, Informetrics, and Citation Studies)
Dr. Samir V. Kamat, Secretary, Department of Defence Research and Development (DDR&D), and Chairman, DRDO, is a distinguished scientist and metallurgist known for his pioneering contributions to advanced materials and defence technologies. This scientometric study examines Kamat’s research output, impact, and collaboration patterns based on publications indexed in Scopus (1987–2022). His 192 publications, spanning 63 different sources, have received 4, 264 citations from 3, 364 citing documents, reflecting substantial scholarly recognition. His H-index of 35 in Scopus signifies a strong and sustained research impact. Collaborative research is evident, with 164 co-authors, and 13.2% international co-authorship, highlighting his global research engagement. The study explores publication productivity, authorship trends, keyword analysis, and research impact across multiple disciplines. These findings provide insights into Kamat’s contributions to defence science and technology in India and beyond.
Keywords: Bio-bibliometrics; Dr. Samir V. Kamat; DRDO; Scientometric portrait; India; South Asia.